PENGELUARAN DAN PEMBEBASAN NARAPIDANA DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19 DI LEMBAGA PEMASYARAKATAN DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Ayu Yosine (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractThe Indonesian government through the Ministry of Law and Human Rights takes steps to minimize the impact of Covid-19 on Prisoners and Detainees in Prisons by granting Assimilation and Integration Rights for Prisoners, this step is carried out by the Ministry of Law and Human Rights by releasing Prisoners to prevent them. the spread of Covid-19. In this decision, the Government's consideration in carrying out the release is due to the high occupancy rate in prisons, so they are vulnerable to contracting the Corona virus. Seeing this impact, issued a Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number M.HH-19.PK.01.04.04 of 2020 concerning the Release and Release of Prisoners through Assimilation and Integration in the Context of Preventing and Combating the Spread of Covid-19. The issues raised in this paper are the Release and Release of Prisoners in the Context of Preventing and Controlling the Spread of Covid-19 in Prisons Can be Justified by Law and There are Special Requirements in the Implementation of the Release and Release of Prisoners in the Context of Preventing and Controlling the Spread of Covid-19 in Correctional Institutions. The type of research used is juridical normative research, legal research which is carried out by examining library materials or secondary materials, with the problem approach used in the writing of this thesis is legislation. The statutory approach is carried out by examining all laws and regulations. The results of the study indicate the provision of assimilation and integration for prisoners through the Minister of Law and Human Rights Regulation Number 10 of 2020 and the Decree of the Minister of Law and Human Rights Number M.HH-19.PK.01.04.04 of 2020. and it can be justified according to law, that almost all prisons in the country are overcapacity, making them vulnerable to the threat of the Corona Virus Diseases (Covid-19) pandemic. Keywords:Prisoner’s Release, Pandemic Covid-19.